THAI GOVERNMENT POLICY IN MANAGE BORDER ISSUE: A case study of Satun (Thailand)-Perlis (Malaysia) - Aiddaris Budiah (MIHI UMY, 2015)
This Thesis will describe about Thai government policy in managing border issue, focusing on case study of the boundary between Wang Prachan (Satun, Thailand) and Wang Kelian (the state of Perlis, Malaysia) by showing about the policy of the countries especially how Thai government policy responds the Malaysia’s new border policy regarding to human trafficking issue. Before Malaysia new border policy, the people come and go without document. So, on 1 April 2015 the Malaysia new border policy forced every people who want to come and go through this border needs to use border pass or passport. This thesis is using descriptive method with qualitative approach. Collecting data technique library research, book, journal, interview and other relevant data to the thesis. The result of this thesis shoed that Thai government respond in two points, the first is Thai government is using the conservative approach through policy in maintaining national security of foreign affair and reducing social inequality by creating opportunities to public service. The second is Thai government is using the accommodative approach by following the Malaysia policy and legitimation to the local government to solve the border issue in Satun (Thailand) and Perlis (Malaysia).